A meta‐analysis of the relationship between empathy and executive function. Issue 1 (8th August 2019) - Yan, Zhiqiang; Hong, Skylar; Liu, Fuli; Su, Yanjie
Abstract: The current meta‐analysis was designed to determine the relationship between executive function (EF) and empathy, as well as to identify any moderators. A search of Chinese and English databases yielded 18 studies and 67 effect sizes involving a total of 6006 participants. Results with the random effects model showed that EF was significantly positively correlated with empathy ( r = .14, p < .001). Subgroup analysis showed that EF was more strongly related to cognitive empathy ( r = .20, p < .001) than to affective empathy ( r = .09, p = .03). Looking at the two dimensions of empathy, we further found that cognitive empathy is closely related to subcomponents of EF, including inhibitory control ( r = .23, p < .001), working memory ( r = .20, p < .001), and cognitive flexibility ( r = .15, p = .036), while only affective empathy was closely related to inhibitory control ( r = .12, p < .001). Results suggested that future research should consider that the relationship between empathy and EF varies depending on the division of specific subcomponents. This finding may help in explaining possible mechanisms of how EF affects empathy.